Feasibility study on the commercialization of Lookee an iOS mobile annotation application - Bautista, Maria Carmina F.; Delmendo, Bryan Dexter H.; Doliro, Glen Mark V.; Ubiadas, Everett C.
"Lookee is not just any other platforms available in the market. Lookee puts intuitive, visual interactivity right at every student's fingertips. Lookee is us because Lookee is the story of every Filipino developer." Everyone had seen the rapid evolution of education system in the Philippines through the years. With the phenomenal invention of iPad by Steve Jobs in 2010, this gives Filipinos the opportunity to integrate advance technologies in education system in the country and also explore the possibility of switching from the old style of teaching by using chalks and blackboards and overhead projectors towards a more innovative and advanced classroom set up with the aid of available software platforms for annotating and file sharing. Tablet devices, such as the Apple's iPad, are seen as having great potential for teaching. With the influx of different gadgets enabling the use of touchscreen technology, making documentation easier without the use of paper and ease the burden of carrying heavy books, more and more educational institutions aim to digitalize lesson plans, class schedules, books and teachers' presentations into files that can be uploaded and be shared with the students quickly. This can be made possible by a software application, or an "app" in common terms, that is able to integrate innovations and conveniences of the emerging technological advancement in the education sector. This app is Lookee. The iOS annotation application is composed of three different products synchronized together into one single mobile application. It is being developed by the company also named Lookee. The algorithm in developing the application was first conceptualized by Dr. Rowell Atienza, Ph.D, a U.P. Professor from the EEE Department Dr. Atienza's vision for Lookee, together with two EEE students, namely Kim and Ryan, was to create an app that will be able to share notes with emphasis on user experience. After receiving a Php 6 million initial investment, Ben Liams, a Filipino-American investor from Singapore, decided to join the team to facilitate project implementation and marketing. There are three identified competitors of the mobile applications available in the Market. These are Bailboard, MightyMeeting, and Nearpod. What sets the product apart from these applications is that Lookee is not just Bailboard which can share file online; not an ordinary Mighty Meeting that enables annotation; and not just like Nearpod that enhanced real-time collaboration. Basically, Lookee is Bailboard plus MightyMeeting plus Nearpod put together to create a platform that will introduce new concept of education condition in the Philippines. More than these, all files are backed up in the cloud. The feasibility study of Lookee, a company that aims to reinvent the education system in the Philippines by developing an interactive iPad app which improves classroom engagement among students and teachers and to create a successful and profitable business that inspires Filipinos to pursue the frontiers of technological innovation, was done to minimize the risk of project failure if implemented, to come up with accurate estimation of resources to be consumed, to justify the investment, and to formulate a working plan for project implementation. The feasibility study was comprised of four phases: market, technical, financial and social profitability analysis. Philippines entered the top 10 fastest growing iOS and Android Markets, with a 181% year-on-year growth rate from October 2011 to October 2012. The potential market of the platform are iPad users in the country and segmented further to students coming from schools which integrated e-learning by using mobile platforms as part of their system. The group has established the secondary target market for the app as the 155.1 million iPad users worldwide. It was then segmented into the primary target market given the nature of the features and purpose of Lookee. Technologically-enabled learning environments were cited as the primary target market at nearly 10 million iPad users and its localization to Filipino users is at 20,000 iPad users. The 17.5% localized primary target market share of 3500 iPad users is the area of concentration of the Market Feasibility Study of Lookee. With these figures growing lucratively year-on-year, there is a market need of developing annotation apps like Lookee. The marketing team should apply the suggested marketing strategies, namely, Search Engine Optimization, Aggregator Sites and Online Review by Professional Bloggers, to be able to tap into the primary target market of technologically-enabled learning environments. As for the localized primary target market, suggested marketing strategies are Direct Selling/Direct Marketing and Education Resellers. Sales Forecasts at the penetration price of 4 dollars amount to a total of Php 22,599,630 at the end of Year 5. Sales and Marketing Costs are estimated at Php 350,160 annually. Competitors were identified as well as Lookee's competitive advantage with respect to these competitors. Competitor Analysis showed the total number of downloads of these competing applications of 857,200 downloads. This is significantly smaller than the nearly 10 million iPad users in schools worldwide. This implies that there is a huge number of technologically-enabled learning environments that still have not used or downloaded annotation applications. As e-learning continues to grow in the Philippines, Lookee's localized market share is expected to grow as well. At a conservative level of sales projections, Lookee is expected to earn a total of Php 22,599,360 for the next five years. Cn the other hand at a pessimistic level of expense projections, the company is expected to spend a total of Php 16,341,277 for the next five years. These figures amount to a total 'profit' of Php 6,258,083, which when added to the initial Php 6,000,000 investment amounts to the 'working capital plus annual sales' value under Year 5. This Php 6,258,083 million 'profit' for the next five years seems quite small considering Lookee had started out with that approximate amount. Nonetheless, Lookee will achieve a return on investment and a positive annual profit at the end of Year 2. Thus, the absolute payback period is 2 years. A downward trend in financial ratios (see Financial Study) is observed starting Year 3. This is primarily because the initial market size of 3,500 users is already well saturated at second quarter of Year 2 and growth in market size is set fixed until Year 5. For the company to become sustainable in the long run, product offerings must be modified. It is more likely that other similar platforms will pop up in the market right after Lookee is introduced. To maintain its competitiveness, the team plans to add core features like the palm rejection technology which enables users to experience the feeling of writing in a paper while using their iPads. The company can also increase its sales by pooling potential users from corporate employees. This is under the assumption that corporate meetings have the same setup as classroom discussions. Furthermore, extending the platform to be readily available to android users can greatly increase its sales. As observed through the years, the market share of android users as opposed to iOS users is increasing from 47.2% in 2012 to 67% in second quarter of 2013. Moreover, there is almost no additional cost in venturing to android platform. The company can make an android version of Lookee using iOS computers which are already in used but not the other way around. This is the beauty of developing an app in iOS before in Android platform. It follows that creating a similar version that will cater the need of android users will surely improve the sales of the company. Through the socio-profitability analysis, the study concludes that Lookee does not only generate profits for its owners but it helps other individuals/companies as well. These include teachers, students, educational institutions, and even the environment through modules / learning curriculums incorporated into Lookee that would greatly help in reducing wastes and consumption of paper. In adherence to national objectives of the country when it comes to education, Lookee promotes improvement in education, which is one of the current administration's goals. As the different NGO's and international organization (i.e. UN Millennium Development Goals) push for greater education prowess in developing countries, Lookee is therefore a worthy investment in providing quality education to the community. Based on the positive projections of financial statements and results from the various tests performed in this phase of the feasibility study, it can be concluded that Lookee is financially feasible.